A survey on container stacking problems based on a conceptual classification scheme: limitations and future trends. (26th October 2022) - Rekik, Ines; Elkosantini, Sabeur
Container stacking problem (CSP) is a challenging task in container terminal management. It consists in assigning containers to locations in a yard terminal. Numerous studies on CSP have been developed according to various objectives and constraints. Despite the widespread literature on this topic, efforts to review and analyse research on CSP are very limited and most of existing reviews treated specific issues, particularly related to stacking operations. For this reason, this survey paper proposes a new conceptual classification scheme, based on content analysis method, to classify and analyse existing literature based on a set of criteria. A special focus is devoted to the analysis of storage rules, which were not exhaustively covered in other surveys. More than 102 papers published on CSP studies within 2000-2020 are classified and analysed based on the suggested conceptual classification scheme. Finally, this paper discusses challenges and highlights research directions that are worth investigation.